The examination of career motivations, experiences and perceptions among Asian American public relations practitioners - Qiu, Jing (Kansas State University, 2011)
This study examines Asian American practitioners’ career motivations, identity-related experiences, and their general perceptions of the public relations industry. Social identity theory serves as the theoretical background of the study, as identity is the core element in understanding practitioners’ working experiences in public relations. A qualitative, in-depth interview method was adopted by the current study. A total of 19 Asian American public relations practitioners were email-interviewed. The study has numerous findings based on the research questions and the emerging themes. In examining why practitioners entered the field of public relations, the study showed that personal interests, industrial attraction, and family influence are key issues in career motivations for practitioners. In examining practitioners’ identities, differences exist between Asians and Asian Americans, and between Asians of different nationalities, although practitioners generally agreed being identified as “Asian Americans”. Their identities had no direct effects on their daily work in public relations; however, subtle challenges and benefits were detected. Challenges facing practitioners were mostly based on stereotypical mindsets, including stereotypes in physical appearance, personality, language and culture. Benefits of being an Asian American in the public relations field included language and cultural advantage, contribution to diversity in the workplace, accessibility to minority organizations, and Asian American unique personal traits. Finally, the study found practitioners’ perceptions of Asian American in public relations were concentrated in the following areas: lacking Asian Americans in the public relations industry, wide opportunities for a career in public relations, professional skills for success in public relations, and increasing Asian American presence in public relations. The current study extends the literature on Asian American public relations practitioners, brings awareness to the subgroup of Asian Americans, and contributes to enhance the presence of Asian Americans to the public relations industry. Strategies of increasing Asian American public relations practitioners are also provided based on participants’ recommendations.
Keywords: Asian American public relations practitioners; Career motivations; Identity-related experiences; Perceptions; Asian American Studies (0343); Communication (0459)